A Quantitative Review of Gender Differences in Vocational Interests in Iceland: Pervasive and Persistent - Sif Einarsdóttir; James Rounds (Nordic Journal of Transitions, Careers and Guidance)
Iceland ranks highly on international indices of gender equality, but the labor market is among the most gender segregated in the world. Gender differences in vocational interests play an important role in explaining these disparities, as interests are highly related to career and educational choices. In this quantitative review, we examine gender differences in both Holland’s RIASEC categories and basic interest scales using data from 10 studies in Iceland. The studies contained populations ranging in age from 13–60 years (N = 9494). Both imported (SII, SDS) and indigenous (Bendill) interest inventories were used to measure interests. First, we found that that the RIASEC scales in the inventories conform to Holland’s structural model both for women and men, except in the youngest age group. Second, and most importantly, the results show the same pattern and extent of mean gender differences that have emerged in other countries. The largest gender differences are in Social interests, which favor women, and Realistic interests, which favor men. Women are also higher on Artistic interests, and men are higher on Investigative and Enterprising interests. These gender differences reflect the gender segregated labor market and educational choices. We discuss the possible influence of sex-role socialization, gender identity, and gender essentialist ideologies on the development of interests and career choices in Iceland. Útdráttur Ísland situr gjarnan í efstu sætunum á alþjóðlegum mælikvörðum um kynjajafnrétti, vinnumarkaðurinn er þó á sama tíma einn sá mest kynjaskipti í heiminum. Þar sem starfsáhugi mótar náms- og starfsval getur kynjamunur í áhuga hjálpað til við að skilja hvers vegna konur og karlar velja ólík störf. Í þessari grein eru niðurstöður 10 rannsókna teknar saman til að kortleggja kynjamun í sex áhugasviðum Hollands – HVLFAS og á 35 undirsviðum. Rannsóknirnar ná til fólks á aldrinum 13 – 60 ára (N = 9494) og eru bæði innfluttar (SDS og Strong) og innlendar (Bendill) áhugakannanir notaðar til að meta starfsáhuga. Í ljós kom að þessar kannanir falla vel að formgerðarlíkan Hollands bæði fyrir konur og karla, nema í allra yngstu aldurshópunum. Kortlagning á kynjamun sýnir álíka mynstur og mikinn kynjamun í áhuga á jafnréttislandinu Íslandi og fram hefur komið í öðrum löndum t.d. Bandaríkjunum. Mestur munur kemur fram á félagssvið þar sem konur eru að jafnaði hærri og á handverkssviði þar sem karlar eru hærri. Konur hafa einnig meiri áhuga á störfum sem falla á listasvið og karlar á störfum á vísinda- og athafnasviði. Kynjamunur í áhuga endurspeglar kynskiptingu íslensks vinnumarkaðar og menntakerfirs. Vísbendingar eru um að mestur munur sé á áhuga kynjanna á unglingsárum en hann minnki með aldrinum og aukinni reynslu. Áhrif kynbundinnar félagsmótunar, sjálfsmyndar og ríkjandi samfélagslegar hugmyndir um ólíkt eðli kynjanna á þróun starfsáhuga og námsval eru ræddar.